Genome-Wide Identification of Circular RNAs Potentially Involved in the Biosynthesis of Secondary Metabolites in Salvia miltiorrhiza - Jiang, Mei; Chen, Haimei; Du, Qing; Wang, Liqiang; Liu, Xinyue; Liu, Chang (Frontiers in Genetics, 2021)
Circular RNAs (circRNAs) play various roles in cellular functions. However, no studies have been reported on the potential involvement of circRNAs in the biosynthesis of secondary metabolites in plants. Here, we performed a genome-wide discovery of circRNAs from root, stem and leaf samples of Salvia miltiorrhiza using RNA-Seq. We predicted a total of 2,476 circRNAs with at least two junction reads using circRNA_finder and CIRI, of which 2,096, 151 and 229 were exonic, intronic and intergenic circRNAs, respectively. Sequence similarity analysis showed that 294 out of 2,476 circRNAs were conserved amongst multiple plants. Of the 55 predicted circRNAs, 31 (56%) were validated successfully by PCR and Sanger sequencing using convergent and divergent primer pairs. Alternative circularisation analysis showed that most parental genes produced two circRNAs. Functional enrichment analyses of the parental genes showed that the primary metabolism pathways were significantly enriched, particularly the carbon metabolism. Differential expression analysis showed that the expression profiles of circRNAs were tissue-specific. Co-expression analysis showed 275 circRNAs, and their parental genes had significantly positive correlations. However, 14 had significantly negative correlations. Weighted gene co-expression network analysis showed that nine circRNAs were co-expressed with four modules of protein-coding genes. Next, we found 416 exonic circRNAs with miRNA-binding sites, suggesting possible interactions between circRNAs and miRNAs. Lastly, we found six validated circRNAs, namely, SMscf2473-46693-46978, SMscf3091-29256-29724, SMscf16-111773-112193, SMscf432-13232-13866, SMscf7007-10563-10888 and SMscf1730-1749-2013, which were originated from the genes involved in the biosynthesis of secondary metabolites. Their parental genes were acetyl-CoA C-acetyltransferase 1 (SmAACT1), 1-deoxy-d-xylulose-5-phosphate synthase 2 (SmDXS2), 4-hydroxy-3-methylbut-2-enyl diphosphate reductase 1 (SmHDR1), kaurene synthase-like 2 (SmKSL2), DWF4 and CYP88A3, respectively. In particular, the correlation coefficient of SMscf2473-46693-46978 and SmDXS2 gene was 0.86 (p = 0.003), indicating a potential interaction between this pair of circRNA and its parent gene. Our results provided the first comprehensive catalogue of circRNAs in S. miltiorrhiza and identified one circRNA that might play important roles in the biosynthesis of secondary metabolites.